2003
DOI: 10.1002/jemt.10406
|View full text |Cite
|
Sign up to set email alerts
|

Transmission electron microscopic observations of membrane effects of antibiotic cecropin B on Escherichia coli

Abstract: The pathway of cell membrane lysis by the peptide antibiotic cecropin B (CB), which contains both a hydrophobic and an amphipathic alpha-helix, was analysed by assessing the morphological changes of Escherichia coli following treatment with the peptide. Exposure of green fluorescent protein (GFP)-expressing E. coli to CB does not lead to an efflux of GFP. Moreover, transmission electron microscopic (TEM) examination of cecropin B-treated cells showed that severe swelling precedes cell death and that the outer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 32 publications
3
27
0
Order By: Relevance
“…Current studies state that AMP-induced bactericidal activity is due to AMP accumulation at the cell surface and formation of transmembrane pores [Brogden, 2005;Chen et al, 2003]. Following treatment with CB, the morphologic differences between the wild-type and mutant strains could be clearly observed under TEM, which showed that the wild-type cells maintained their integrity to a much greater extent as compared to the mutant strain.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Current studies state that AMP-induced bactericidal activity is due to AMP accumulation at the cell surface and formation of transmembrane pores [Brogden, 2005;Chen et al, 2003]. Following treatment with CB, the morphologic differences between the wild-type and mutant strains could be clearly observed under TEM, which showed that the wild-type cells maintained their integrity to a much greater extent as compared to the mutant strain.…”
Section: Discussionmentioning
confidence: 77%
“…The extent of cell swelling was more pronounced in the mutant strain than in the wild-type strain. A previous study also found that CB treatment displaced and distended the outer membrane of E. coli [Chen et al, 2003]. We may conclude that H. parasuis is more sensitive to CB killing following deletion of the HAPS_2096 gene.…”
Section: Discussionmentioning
confidence: 82%
“…It is difficult for the pathogen to develop resistance against the cecropin-like peptides in planta. Several previous studies have indicated that CB-derived peptides possess in vitro activity against several bacterial and cancer cells (10,11). Furthermore, the antibacterial activities of synthetic CB against some well-known Gram-negative bacteria, such as E. coli, S. enteritidis, K. pneumoniae, and P. aeruginosa, were investigated in the current experiments.…”
Section: Discussionmentioning
confidence: 95%
“…CB has long been reported to possess lytic activity against several Gram-negative bacteria, such as E. coli, Salmonella enteritidis, Klebsiella pneumoniae, and Pseudomonas aeruginosa (10,11). To confirm that CB would provide protection against major bacterial diseases of the tomato, the effectiveness of a synthetic CB peptide against two common tomato pathogens, R. solanacearum and X. campestris pv.…”
Section: Resultsmentioning
confidence: 99%
“…Hecate-CGb conjugate (H-CGb-c) selectively kills tumor cells expressing Lhcgr but spares the healthy receptor-positive and -negative cells (Leuschner et al 2001, Bodek et al 2005b. The cytotoxic activity of the H-CGb-c induces plasma membrane disruption within minutes (Chen et al 2003, Bodek et al 2005b, Hansel et al 2007b, it is not antigenic, and it has not been shown to have any clear side effects (Bodek et al 2005b, Hansel et al 2007b, Vuorenoja et al 2008). H-CGb-c has been found to selectively kill Lhcgr expressing prostate (Hansel et al 2001, Leuschner et al 2001, Bodek et al 2005a, mammary gland (Bodek et al 2003, Leuschner et al 2003, Zaleska et al 2004, Leuschner & Hansel 2005, Hansel et al 2007a, ovarian (Gawronska et al 2002, Bodek et al 2005b, and testicular cancer cells (Bodek et al 2005b).…”
Section: Introductionmentioning
confidence: 99%